2002
DOI: 10.1021/jm0109863
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporins:  Structure−Activity Relationships for the Inhibition of the Human MDR1 P-Glycoprotein ABC Transporter

Abstract: Cyclic undecapeptide cyclo-[MeBmt(1)-Abu(2)-MeGly(3)-MeLeu(4)-Val(5)-MeLeu(6)-Ala(7)-D-Ala(8)-MeLeu(9)-MeLeu(10)-MeVal(11)], the immunosuppressive and antifungal antibiotic cyclosporin A (CsA), was reported to interfere with the MDR1 P-glycoprotein (Pgp), a transmembranous adenosine 5'-triphosphate binding cassette (ABC) transporter with phospholipid flippase or "hydrophobic vacuum cleaner" properties that mediate multidrug resistance (MDR) of cancer cells. By use of photoaffinity-labeled cyclosporins and memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 52 publications
3
91
0
1
Order By: Relevance
“…Therefore, we prepared PMs from DOX40 cells to further characterize PK11195 binding in Pgp-expressing cells and documented that PM fractions contained Pgp but were depleted of mitochondrial inner and outer mitochondrial membrane markers ( Figure 6A). DOX40 PM fractions showed specific 3 H-CSA binding, consistent with documented Pgp binding by CSA, 31,32,[43][44][45][46][47][48][49][50][51] and specific 3 H-PK11195 binding was also reproducibly measured in DOX40 PMs. Specific PK11195 binding that was measured in 8226 PM assays (data not shown) suggests that pBR can be PM-localized, consistent with other reports.…”
Section: Pk11195 Binds Pgp At Binding Sites Distinct From Those Boundsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, we prepared PMs from DOX40 cells to further characterize PK11195 binding in Pgp-expressing cells and documented that PM fractions contained Pgp but were depleted of mitochondrial inner and outer mitochondrial membrane markers ( Figure 6A). DOX40 PM fractions showed specific 3 H-CSA binding, consistent with documented Pgp binding by CSA, 31,32,[43][44][45][46][47][48][49][50][51] and specific 3 H-PK11195 binding was also reproducibly measured in DOX40 PMs. Specific PK11195 binding that was measured in 8226 PM assays (data not shown) suggests that pBR can be PM-localized, consistent with other reports.…”
Section: Pk11195 Binds Pgp At Binding Sites Distinct From Those Boundsupporting
confidence: 61%
“…CSA and many other efflux modulators bind transporters directly. 31,32,[43][44][45][46][47][48][49][50][51] First, we asked whether PK11195 binds Pgp, first by comparing PK11195 binding in 9 primary AML samples for which additional aliquots were available. CSA and PK11195 had increased dye retention in 5 of these samples (Pgp-positive AMLs), whereas 4 samples showed no efflux capacity (Pgp-negative AMLs).…”
Section: Pk11195 Efficiently Sensitizes Cancer Cells To Mit a Clinicmentioning
confidence: 99%
“…It is now known that CsA inhibits both P-gp (Loor et al, 2002) and also BCRP, albeit at lower affinity (Gupta et al, 2006;Matsson et al, 2009). Application of high-dose (50 M) CsA abolished net secretory ciprofloxacin flux in bcrp1-MDCKII cells (from 0.24 Ϯ 0.02 to 0.04 Ϯ 0.02 nmol ⅐ cm Ϫ2 ⅐ h Ϫ1 , n ϭ 3; P Ͻ 0.05 versus controls) but inhibited only a fraction of net secretory flux in low passage Caco-2 cell monolayers (from 0.39 Ϯ 0.06 to 0.22 Ϯ 0.04 nmol ⅐ cm Ϫ2 ⅐ h Ϫ1 , n ϭ 3; P Ͻ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…CsA is much less potent than CsH in inhibiting fMLF-induced superoxide production (11). Furthermore, although more recent studies demonstrated the inhibition of fMLF-induced degranulation by CsA and its analogues, it remains unclear whether the receptor or a signaling pathway was targeted by these cyclosporins (14,29). Several immunosuppressants have been shown to inhibit mast cell degranulation induced by FcRI cross-linking (27,30), an effect apparently mediated through a mechanism shared among these agents and related to their immunosuppressive properties (15).…”
Section: Discussionmentioning
confidence: 99%